FILSAFAT DALAM ILMU EKONOMI (SEBUAH JAWABAN MENGAPA ILMU EKONOMI BERFILSAFAT) - Misbahuddin Misbahuddin (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2012)
Humans are the creators and problem solvers. Of our problem was solved, regardless of the type and shape. So we live on the stack problem. Humans are always in conflict with himself and his environment, because of the causal relationship, coupled with the needs facing ketidaktercapaiannya. With the help of these economics, Humans develop their potential to address the needs of this survival. He thought of new things, because he lives not just for survival, but more than that. Humans develop the culture, people give meaning to life, humans